Clinical and genetic characterization of Lenz-Majewski syndrome with a PTDSS1 variant: a case report and literature review - Zhang, Yahua; Wu, You; Yan, Lulu; Zhang, Yuxin; Li, Haibo; He, Yan (Frontiers in Pediatrics, 2025)
IntroductionLenz-Majewski syndrome (LMS) is an ultra-rare congenital disorder with progressive skeletal dysplasia, cutis laxa, and intellectual disability, typically caused by pathogenic variants in the PTDSS1 gene.MethodsOur patient with multiple malformations and developmental delay who was treated at the Women and Children's Hospital of Ningbo University in September 2023 was selected as the research subject. Whole exome sequencing (WES) technology was used to test the child, and Sanger sequencing verification and pathogenicity analysis were carried out for the suspected variations.ResultsWe report the first molecularly confirmed case of LMS in a Chinese patient, a male infant presenting with classic features such as craniofacial dysmorphism, hyperostosis, loose skin, syndactyly, and short stature, together with mild global developmental delay and thyroid dysfunction. Whole exome sequencing (WES) identified a heterozygous c.806C > T (p. Pro269Leu) variant in the PTDSS1 gene, which was validated by Sanger sequencing and functionally assessed for pathogenicity. We further reviewed 12 previously reported cases with PTDSS1 variants and compared phenotypes, highlighting both shared and unique features.DiscussionThis case expands the ethnic and phenotypic spectrum of LMS and reinforces the association between the c.806C > T (p. Pro269Leu) variant and LMS. Early genetic testing facilitates recognition of atypical presentations and enables timely diagnosis and management.